2019
DOI: 10.1007/s10503-019-09497-9
|View full text |Cite
|
Sign up to set email alerts
|

Dialectical Models of Deliberation, Problem Solving and Decision Making

Abstract: Hamblin distinguished between formal and descriptive dialectic. Formal normative models of deliberation dialogue have been strongly emphasized as argumentation frameworks in computer science. But making such models of deliberation applicable to real natural language examples has reached a point where the descriptive aspect needs more interdisciplinary work. The new formal and computational models of deliberation dialogue that are being built in computer science seem to be closely related to some already existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
4
0
1
Order By: Relevance
“…The results revealed that the problem-solving schema is significant with a high standardized frequency in the debating discourse. This finding is congruent with previous research that has found debating practice beneficial for generating and organizing ideas on solving problems (Eckstein & Bartanen, 2015;Ma, 2017;Walton et al, 2019;Yulia & Aprilita, 2018). Additionally, the type-token ratio in the compiled learner corpus is much higher than in the British National Corpus.…”
Section: Debating Corpus Implicationsupporting
confidence: 91%
“…The results revealed that the problem-solving schema is significant with a high standardized frequency in the debating discourse. This finding is congruent with previous research that has found debating practice beneficial for generating and organizing ideas on solving problems (Eckstein & Bartanen, 2015;Ma, 2017;Walton et al, 2019;Yulia & Aprilita, 2018). Additionally, the type-token ratio in the compiled learner corpus is much higher than in the British National Corpus.…”
Section: Debating Corpus Implicationsupporting
confidence: 91%
“…Among the significant contributions in designing computational dialogue systems, Walton's research provided fundamental insight in how deliberation unfolds, leading to differences in how protocol rules are set out (Atkinson et al 2013;Walton 2006. His views deliberation as a dynamic process of identification of alternatives, consideration of new information that changes the current circumstances leading to a revision of the issue set out at the initial stage (Walton et al 2019). This affects structural rules of the dialogue, termination conditions as well as the allocation of global and local burden of proof (Atkinson et al 2013;Walton et al 2015Walton et al , 2019).…”
Section: Extending the Boundaries Of Argumentation Theorymentioning
confidence: 99%
“…His views deliberation as a dynamic process of identification of alternatives, consideration of new information that changes the current circumstances leading to a revision of the issue set out at the initial stage (Walton et al 2019). This affects structural rules of the dialogue, termination conditions as well as the allocation of global and local burden of proof (Atkinson et al 2013;Walton et al 2015Walton et al , 2019). Walton's deliberation models provide opportunities to develop agent dialogues with richer elements which are closer to natural deliberation and can provide support to human deliberation in a more effective way .…”
Section: Extending the Boundaries Of Argumentation Theorymentioning
confidence: 99%
“…We have published articles on formal models of deliberation dialogue. A recent example of this work (Walton, Toniolo and Norman, 2019), carried out with Professor Tim Norman of the University of Southampton, builds a typology of deliberation dialogues by presenting a series of realistic examples of deliberation in the tradition of Hamblin (1970, 256). The observations from our examples are used to suggest that in order to better understand and contextualise the argumentation components that make up realistic deliberations, it is necessary to carefully distinguish between two species of deliberation called problem solving deliberation and decision making deliberation.…”
Section: Young Logicians and Computer Scientistsmentioning
confidence: 99%